LINGUISTIC RESILIENCE: A SOCIOLINGUISTIC STUDY OF LANGUAGE MAINTENANCE AND IDENTITY NEGOTIATION IN A MARGINALIZED URBAN COMMUNITY - Novi Ulfa Safitri; Sara Hussain; Marwati Marwati; Sitti Agustina (Lingeduca: Journal of Language and Education Studies, 2025)
Marginalized urban communities face linguistic pressures threatening their heritage languages. This study examines language preservation in environments where language is a key site of identity struggle. This sociolinguistic research investigates the specific strategies of language maintenance and identity negotiation utilized by a marginalized urban community, aiming to identify key factors enabling linguistic resilience against dominant language encroachment. A qualitative ethnographic approach was employed, using participant observation and in-depth sociolinguistic interviews (n=45). The analysis focused on language choice across social domains and the metalinguistic narratives speakers used to articulate identity. Findings indicate resilience is achieved through “covert maintenance,” reinforcing the heritage language in private domains as resistance. Identity negotiation is fluid, with strategic code-switching used to signal affiliation. Public language use showed assimilation, but private use demonstrated strong vitality.  Linguistic resilience in this community is a conscious act of social agency and identity negotiation, not passive retention. The community preserves its language through strategic domain management, proving vitality is inextricably linked to identity.